Lafoeina longitheca Jaderholm 1904 - OLIVEIRA, OTTO M. P.; MIRANDA, THAÍS P.; ARAUJO, ENILMA M.; AYÓN, PATRICIA; CEDEÑO-POSSO, CRISTINA M.; CEPEDA-MERCADO, AMANCAY A.; CÓRDOVA, PABLO; CUNHA, AMANDA F.; GENZANO, GABRIEL N.; HADDAD, MARIA ANGÉLICA; MIANZAN, HERMES W.; MIGOTTO, ALVARO E.; et al. (Zenodo, 2016)
Lafoeina longitheca Jäderholm, 1904a Distribution in South America: polyp—Pacific Ocean, Chile, from 48°S to 49°S, and at 53.78°S 70.97°W (Galea 2007 p. 38; Galea et al. 2009a p. 328; Galea et al. 2012a p. 24); Atlantic Ocean, at South Georgia Island (Jäderholm 1905; Blanco 1994a). Habitat: polyp—from 10 to 74m depth, on Bougainvillia muscus (Blanco 1994a; Galea 2007 p. 38; Galea et al. 2009a p. 328). Published as part of OLIVEIRA, OTTO M. P., MIRANDA, THAÍS P., ARAUJO, ENILMA M., AYÓN, PATRICIA, CEDEÑO-POSSO, CRISTINA M., CEPEDA-MERCADO, AMANCAY A., CÓRDOVA, PABLO, CUNHA, AMANDA F., GENZANO, GABRIEL N., HADDAD, MARIA ANGÉLICA, MIANZAN, HERMES W., MIGOTTO, ALVARO E., MIRANDA, LUCÍLIA S., MORANDINI, ANDRÉ C., NAGATA, RENATO M., NASCIMENTO, KARINE B., JÚNIOR, MIODELI NOGUEIRA, PALMA, SERGIO, QUIÑONES, JAVIER, RODRIGUEZ, CAROLINA S., SCARABINO, FABRIZIO, SCHIARITI, AGUSTÍN, STAMPAR, SÉRGIO N., TRONOLONE, VALQUÍRIA B. & MARQUES, ANTONIO C., 2016, Census of Cnidaria (Medusozoa) and Ctenophora from South American marine waters, pp. 1-256 in Zootaxa 4194 (1) on page 143, DOI:10.11646/zootaxa.4194.1.1, http://zenodo.org/record/10068449